Intergenerational continuity of crime among children of organized crime offenders in the Netherlands - van Dijk, Meintje (Crime, law and social change, 2022)
As existing literature on intergenerational continuity of criminal behavior is mainly based on data on ‘general’ offenders and their children, the current study aims to improve our knowledge by looking at intergenerational continuity of crime among a national sample of children of organized crime offenders. Judicial data on all (N= 478) offenders convicted of organized crime in the Netherlands (in the period 2008 - 2014) and their children were used to study offspring’s involvement in crime. In addition, a comparison group was selected from the entire population in the Netherlands to examine the relative risk of offending. Results show that almost half of the children of organized crime offenders have a criminal record. Sons are significantly more at risk of offending and this risk also increases strongly by age. Furthermore, the results show the strongest intergenerational relation for violent crimes. Gender of the convicted parent and timing of parental crime also seem to play a role in the continuity. With regard to the relative risk of offending, the results show that children of convicted organized crime offenders are three times more at risk of offending compared to children in the comparison group, even after controlling for the number of parental crimes. In sum, there is a substantial risk of intergenerational continuity of criminal behavior among children of organized crime offenders. Future research would benefit from focusing on how criminal behavior in these specific families is transmitted to future generations.